Performance Assessment in Courts - The Swiss Case - Andreas Lienhard (International Journal for Court Administration, 2014)
Abstract  Performance assessments have become commonplace in management, even in the public sector. With the increasing pressure on courts to perform while making efficient use of resources, performance assessments in the justice system are also gaining in importance. However, the need for judicial independence poses special challenges for performance assessments in courts.  Against this background, this article conducts a constitutional appraisal, and contrasts the need for judicial independence with the principles governing effectiveness and efficiency, self-government and supervision, and appointment and re-appointment. A duty to guarantee justice can be derived from this that does not in principle exclude the performance assessment of judges, but even renders it essential, subject to compliance with certain requirements.  In these circumstances, it seems hardly surprising that numerous countries conduct performance assessments of judges and also that various international institutions have developed principles for this purpose, a summary of which is presented – in Switzerland’s case based on a recently conducted survey.  In the field of conflict between the guaranteeing justice and protecting the judiciary, the following key questions arise in particular:  What is the purpose of performance assessments and what are the consequences? What is subjected to a performance assessment and what are the assessment criteria? How is performance recorded as the basis for the performance assessment? Who is subjected to a performance assessment, and must a distinction be made between judges in higher and lower courts? Who carries out the performance assessment and what methods of protecting one’s rights are available? Who should receive the results of the performance assessment? The contribution sketches out possible answers to these key questions and aims to encourage academics and practitioners to give further consideration to this subject.